2014
DOI: 10.1021/ja504441h
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Role of Water in Biological Function: Studying Solvated Biomolecules Using Terahertz Absorption Spectroscopy in Conjunction with Molecular Dynamics Simulations

Abstract: In life science, water is the ubiquitous solvent, sometimes even called the "matrix of life". There is increasing experimental and theoretical evidence that solvation water is not a passive spectator in biomolecular processes. New experimental techniques can quantify how water interacts with biomolecules and, in doing so, differs from "bulk" water. Terahertz (THz) absorption spectroscopy has turned out to be a powerful tool to study (bio)molecular hydration. The main concepts that have been developed in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 257 publications
(152 citation statements)
references
References 57 publications
(124 reference statements)
7
142
1
2
Order By: Relevance
“…In contrast, the physical community can probe water in many different ways (Table 1). In addition to these, other potentially useful techniques include optical Kerr effect, and narrow/broad band THz/far-IR spectroscopy, 71 and more established techniques such as NMR relaxation measurements using H 2 17 O, electron spin resonance (ESR) and electron nuclear double resonance (ENDOR). En masse, these techniques have emphasized or raised many questions about the nature and implications of the related topics of 'highly structured' water, high X-ray occupancy, and water molecules of limited translational and rotational motion.…”
Section: [Insert Table 1]mentioning
confidence: 99%
“…In contrast, the physical community can probe water in many different ways (Table 1). In addition to these, other potentially useful techniques include optical Kerr effect, and narrow/broad band THz/far-IR spectroscopy, 71 and more established techniques such as NMR relaxation measurements using H 2 17 O, electron spin resonance (ESR) and electron nuclear double resonance (ENDOR). En masse, these techniques have emphasized or raised many questions about the nature and implications of the related topics of 'highly structured' water, high X-ray occupancy, and water molecules of limited translational and rotational motion.…”
Section: [Insert Table 1]mentioning
confidence: 99%
“…The low frequency modes of proteins and water can couple very effectively with a rapid energy flow between the protein and the water network modes. 1 The last years have witnessed a combined effort to develop new experimental tools in the THz range accompanied by the evolution of simulation tools for the description of the coupled solute/hydration dynamics. The information in this spectral frequency range allows an unprecedented view on the interplay of protein dynamics and hydration dynamics during molecular recognition.…”
Section: B Thz Spectra Of Proteins In Aqueous Solutionmentioning
confidence: 99%
“…1,[30][31][32] The sensitivity of the THz range to changes in hydration dynamics stems from the fact that the collective network motions of water, e.g., hydrogen bond rearrangements, translational and rotational relaxation, lie in the frequency range from 1 to 6 THz.…”
Section: B Thz Spectra Of Proteins In Aqueous Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, qualitatively, we find clear significant differences for water retardation at the active site. Furthermore, when we analyzed the predicted vibrational density of states, we found that the single-stranded substrate shows an increased amount of lower energies modes as expected for a more flexible structure compared with the triple-helical substrate (34). Most importantly, we observed a correlation between the vibrational Fig.…”
Section: Changes In Enzyme-substrate-water-coupled Motions Persist Wellmentioning
confidence: 53%